Europe 2020 Strategy and Structural Diversity Between Old and New Member States. Application of zero-unitarizatin method for dynamic analysis in the years 2004-2013 - Adam P. Balcerzak (Institute of Economic Research (IER), 2015)
In the year 2015 the European Union has reached the halfway of implementation of Europe 2020 strategy, which is aimed at forming the conditions for sustainable and inclusive economy delivering high levels of employment, productivity and social cohesion. In this context the aim of the paper is to analyze the level of fulfillment its aims with special concentration on diversity between New Member States that joined European Union in 2004 and 2007 (EU-10) and Old European Union Members (EU-15). The empirical part of the paper is based on the taxonomic research with application of zero-unitarization method. In order to make the dynamic analysis for the years 2004-2013 the constant reference point for the whole period was used. The evaluation was based on the Eurostat Europe 2020 indicators. The analysis showed significant diversity between New and Old Member States. However, in the years 2004-2013 EU-10 had made an important progress in the implementation of Europe 2020 strategy.
Keywords: C00; E61; O52; 330; Europe 2020 strategy; multivariate analysis; zero-unitarization method